Liquidation, fire sales, and acquirers’ private information - Nishihara, Michi; Shibata, Takashi (Journal of economic dynamics & control, 2019)
We develop a dynamic model in which a distressed firm optimizes an exit choice between sell-out and default as well as its timing. We assume that the distressed firm is not informed about the acquirer’s asset valuation. We show that the firm delays liquidation to decrease the acquirer’s information rent. Notably, the firm can change the exit choice from sell-out to default when the screening cost is high. In this case, shareholders declare default regardless of the acquirer’s valuation, which provides the acquirer the maximum information rent. Together with the deadweight costs of bankruptcy, the maximal information rent, which causes a wealth transfer from debt holders of the bankrupt firm to the acquirer, lowers the sales price and debt recovery. This mechanism can explain many empirical findings about fire sales and acquirers’ excess gains. Higher volatility, leverage, and asymmetric information increase the likelihood of a fire sale, but higher bankruptcy costs could play a positive role in preventing a fire sale. With asymmetric information, the firm can reduce debt issuance to avoid the risk of a fire sale.